Peningkatan Pengetahuan Ibu Hamil Trimester I tentang Penurunan Mual dan Muntah dengan Akupresur Pericardium 6 - Gustina, Gustina; Nurbaiti, Nurbaiti (Universitas Baiturrahim, 2024)
Excessive nausea and vomiting result in a weak body, pale face and the frequency of urination decreases drastically so that body fluids are reduced, blood becomes thick (hemoconcentration) and can slow down blood circulation which means that oxygen consumption and tissue food are also reduced. The first trimester is the period when the fetus is in the early stages of the formation of body organs, if the mother suffers from excessive nausea and vomiting, it will result in the mother's nutrition not being met, this has a bad impact on the developing fetus, including causing slow fetal growth and BBLR. One of the non-pharmacological treatments to reduce nausea and vomiting is acupressure. Acupressure therapy to reduce nausea and vomiting is carried out by manually pressing on the pericardium 6 (PC 6) point in the wrist area. The purpose of this community service is to increase the knowledge of pregnant women in the first trimester about reducing nausea and vomiting with Pericardium 6 (Pc 6) acupressure. The activity method, carried out from February to August 2023 at PBM Yustati Ambarita, Jambi City, is a form of educational activity for pregnant women in the first trimester. After the education, a posttest was carried out using the same questionnaire with the pretest. The results of the education showed an increase in maternal knowledge after participating in the education. Before the education, 11 mothers had good knowledge and 19 mothers had poor knowledge. After education, all mothers have good knowledge about pericardium acupressure to overcome nausea and vomiting in pregnant women in the first trimester.